(untitled) (Bangladesh Journal of Plant Taxonomy, 2022)
The ectomycorrhizae of a newly described club fungus Clavariadelphus pakistanicus were collected from Ayubia, Khyber Pakhtunkhwa, Pakistan and described morpho-anatomically. Its Pinus wallichiana associated ectomycorrhizae has been characterized by dichotomously branched, reddish brown color of mature and dark brown to blackish young ectomycorrhizal tips with frequent unbranched and septate emanating hyphae. During molecular and phylogenetic analyses, these mycobionts showed maximum similarity and were clustered with basidiocarps sequences of C. pakistanicus. Hence it was confirmed that these ectomycorrhizae belong to C. pakistanicus and being first time reported from Pakistan. Bangladesh J. Plant Taxon. 29(1): 129-136, 2022 (June)